Las actividades lúdicas como medio para el interaprendizaje de la natación en niños de 6 a 8 años de la Escuela Simón Bolívar“, provincia de Cotopaxi, cantón Latacunga, parroquia La Matriz en el año lectivo septiembre 2013, febrero 2014 - Arequipa Guanoluisa, Miguel Armando (2015)
This research was aimed at the realization of recreational activities because one Lack of Teaching Children swimming, so a rise that school do not practice esta discipline is of great importance, which has caused lost by lack of interest of the Masters, had a direct impact on the integral formation of children of the School "Simon Bolivar" of Cotopaxi Latacunga Canton Province in the academic year in September 2013- February 2014, researchers concerned esta problem with the vision of creating awareness among authorities, teachers, parents and family, proposed paragraph to solution one esta Problem developing a guide of leisure activities, practice esta discipline, it helps to implement the curriculum reform, sports recreation Should you tomandas by Party the good life, moreover serve as a guide esta paragraph Maestro Improve teaching and learning processes of Children Institution, since in the hours classes will be able to be applied to educational needs….